Political mobilization of grassroots women and its implications: a case study of Proshika in Bangladesh - Md. , Moniruzzaman (GSID, Nagoya University, 2004)
Proshika, the second largest NGO in Bangladesh, follows the participatory development approach for the socioeconomic development and empwoerment of poor women in Bangladesh. However, proshika is heavily criticized and opposed by some quaters especially Islamic groups for its alleged controvertial activities. This paper examines Proshika's participatory mobilization activities with reference to a specific women's mobilization incident in 1998, the final objective being to underline the implications of NGO-led political mobilization of women in Bangladesh. The paper argues that proshika's top-down approach to decision-making and its impositional type of mobilization is heavily loaded with partisan political rhetoric. It implies that political mobilization as a means of political empowerment for women may not be as simple as women's empowerment theories suggest.